Family Resilience in a Psychological Perspective in Indonesia - Fitria, Ida; Zainuddin, Muslim; Julianto, Julianto; Aliana, Cut Rizka; Barlian, Nur Intan (El-Usrah: Jurnal Hukum Keluarga, 2024)
A happy family is not one that experiences no issues in everyday life. A happy family still needs the key to the strength and happiness through resilience, i.e., the ability of a family to survive from difficult challenges. This study aims to discuss family resilience from the perspective of Indigenous psychology in Aceh. The study used qualitative and quantitative methods with open coding data analysis. The participants in this study were husbands or wives of Aceh, Gayo, and Javanese tribes totaling 146 participants. The participants were grouped into three categories, i.e., the elderly couples (15%, n=22), middle-aged couples (46%, n=67), and newly married couples (39%, n=57). The results of the qualitative data analysis on how to recover from adversity in the family (i.e., family resilience) from the Indigenous perspective on the elderly couples, starting from the most dominant, are “communicating well” (31.8%), “praying and worshiping” (18.2%), and “being patient” (18.2%), while the rest mentioned “giving in, forgiving, children, and family support”, among others. Further, the middle-aged couples also showed the dominant responses for “communicating well” (28.4%), “self-introspection” (14.9%), and “praying and worshiping” (10.4%), while the rest had lower proportions. Newly married couples also indicated higher percentages in “communicating well” (36.8%), “praying and worshiping” (28.1%), and “self-introspection” (8.8%), whereas other responses had lower percentages. In general, the findings reveal that “communicating well” (32.0%), “praying and worshiping” (16.3%), “self-introspection” (12.2%), and “being patient” (8.2%) are the renewal aspects of resilience from the Indigenous perspective. This suggests that the resilience of married couples in Aceh not only relies on their ability to recover or to be resilient on their own, but also puts more emphasis on mutual communication, praying, and worshiping. Bonanno's approach emphasizes resilience in aspects of tough personality, self-improvement and repressive self-adjustment.